Pengembangan Bahan Ajar Matematika Berbasis Daring Untuk Meningkatkan Kemampuan Pemecahan Masalah - Huda, Irkham Abdaul; Astuti, Suhandi (Pendidikan Matematika Universitas PGRI Yogyakarta, 2021)
The objectives of this study are (1) to develop online-based mathematics teaching materials to improve problem-solving skills in distance learning in the pandemic era and (2) to determine the level of validation of the development of online-based mathematics teaching materials to improve problem-solving skills based on expert validation tests. This R&D research uses the ADDIE model which consists of analysis (analysis), design (planning), development (development), implementation (implementation), and evaluation (evaluation). However, the implementation in this research only reached the development stage. The subjects of this study were class teachers and 5th grade students of SD Negeri Plumutan, Bancak, Semarang Regency. The results of this study are (1) there are three stages in this research and development, namely analyzing the characteristics and initial abilities of students, planning and making teaching materials with the weebly website, and developing by conducting expert validation tests. (2) based on the validation test, material experts give a percentage of 85% with the criteria of